PERBEDAAN SEBELUM DAN SESUDAH DIBERIKAN EDUKASI GIZI DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN DAN POLA ASUH MAKAN IBU PADA BALITA STUNTING - Naufalia Primandita Arie Prasetiawan; Ibnu Fajar; Bastianus Doddy R (Politeknik Kesehatan Kemenkes Malang, 2022)
Background: Stunting is a condition where toddlers have a length or height that is less than their age. This condition is measured by a length or height that is more than minus two standard deviations of the WHO child growth standard median. Stunting is caused by several factors. The causes are poor practice, limited health services, lack of access for families to consume nutritious food, and lack of access to clean water and sanitation.. Objective: This study aims to determine the difference between nutrition education and booklet media on the knowledge and feeding patterns of mothers with stunting toddlers. Methods: This research is included in the literature study research or systematic review. Systematic literature review or often abbreviated as SLR or in Indonesian called systematic literature review is a literature review method that identifies, assesses, and interprets all findings on a research topic, to answer research questions that have been previously determined. Results The average knowledge before giving education using booklets tends to be low, but after giving education using booklets it is proven to be effective in increasing parents' knowledge about caring for stunting toddlers. Another result is that before the intervention education was given as many as 9 respondents (20 percent) in the poor category, 29 respondents (64.5 percent) had sufficient knowledge in the good category, 7 respondents (15.5 percent) in the good category. After the intervention, 34 respondents (75.6 percent) had knowledge in the good category, 8 respondents (17.7 percent) in the sufficient category, and 3 respondents (6.7 percent) in the poor category. Conclusions: There is a difference in the knowledge of mothers of stunting toddlers before and after being given nutrition education with booklet media. Statistically it also shows a significant change in the knowledge of mothers of stunting toddlers after being given nutrition education with booklet media. Keywords : Booklet, Stunting, Nutrition, and Literature Review